Anti Hepatitis E Virus Seropositivity in a Group of Blood Donors - S Aminiafshar; M Alimagham; L Gachkar; F Yousefi; Z Attarchi (Tehran University of Medical Sciences, 2004)
Type E hepatitis is caused by an unclassified virus producing acute self-limited hepatitis in different parts of the world. In order to estimate the prevalence of hepatitis E virus seropositivity in Tehran blood donors, a cross- sectional study was performed by the enzyme immunoassay method from 2003 to 2004 in a group of 90 blood donors. We noticed that 7 cases (7.8%) were anti-HEV Ab positive. This figure correlates with the prevalence ratio of endemic parts. There was no association between seropositivity and sex. The commonest age group was 40-49 years. We conclude that Iran can be considered as an endemic area for type E hepatitis (prevalence>5%), and type E hepatitis is more common in Iran than Israel and Turkey, but less common than Saudi Arabia, Iraq and Pakistan; therefore, it should be regarded in the differential diagnosis of acute hepatitis.